HEAT TRANSFER ENHANCEMENT OF A FREE CONVECTIVE SOLAR AIR HEATER USING CONICAL PIN TURBULATORS - GILANI, SYED EHSAN-UL-HAQ (2016)
The process of heat transfer between a hot surface and a flowing cold air has many applications in both the domestic and industrial area, in heat exchangers or for surface cooling. To increase the efficiency of this process, small sized turbulators have been used on the hot surface so that the turbulators break the viscous laminar layer/sub-layer of the fluid flowing over the surface. However, they come at a cost of pressure drop. The turbulators have existed for some time now but unfortunately up until now they are only used in application whereby the fluid flow is under force convection for which external power is required. In this study, a special test rig is designed and fabricated to test the effect of these turbulators under free convective fluid flow, whereby no external power is required. The turbulators used in this project are conical shaped pins and their effect on convective heat transfer rate and thermal efficiency was studied. The test rig was a special type of free convective solar air heater comparing 6 different type of absorber plates at once. Optimum inclination angle of the absorber plate was found to be 45º and staggered arrangement of conical pins were found to be more effective compared to inline arrangement. A total of three different pitch of conical pins (16 mm, 32 mm & 48 mm) and three different heights of conical pins (2 mm, 3 mm & 4 mm) were tested all in staggered conical pin arrangement with an average systematic uncertainty of ± 6.4%. The results showed that pin pitch of 16 mm increased the Nusselt number the most followed by 32 mm and 48 mm pitch. The efficiency was also increased by up to 26.5 % for absorber plate with 16 mm pin pitch as compared to smooth flat plate. The pin height of 4 mm was found to be the best in enhancing the Nusselt number. In the end of this study, a correlation was developed to predict the Nusselt number for conical pin protruded plates of dimensional ranges (16 mm < pin pitch < 48 mm) and (2 mm< pin height < 4 mm) under free convective flow. A correlation comprising of all the operational and design parameters has been generated for staggered arrangement. The accuracy of the correlation for the entire experimented range is ±25 %, and at optimum operating parameters, it is reduced to ±5.6 %.